New Insights Into the Pathogenesis of Bullous Pemphigoid: 2019 Update - Genovese, Giovanni; Di Zenzo, Giovanni; Cozzani, Emanuele; Berti, Emilio; Cugno, Massimo; Marzano, Angelo Valerio (Frontiers in Immunology, 2019)
There are several lines of evidence indicating that the physiopathological bases of bullous pemphigoid (BP), the most common subepidermal autoimmune bullous disease, are hallmarked by the production of autoantibodies directed against the hemidesmosomal anchoring proteins BP180 and BP230. In contrast to the robustness of the latter assumption, the multifaceted complexity of upstream and downstream mechanisms implied in the pathogenesis of BP remains an area of intense speculation. So far, an imbalance between T regulatory cells and autoreactive T helper (Th) cells has been regarded as the main pathogenic factor triggering the autoimmune response in BP patients. However, the contributory role of signalling pathways fostering the B cell stimulation, such as Toll-like receptor activation, as well as that of ancillary inflammatory mechanisms responsible for blister formation, such as Th17 axis stimulation and the activation of the coagulation cascade, are still a matter of debate. In the same way, the pathomechanisms implied in the loss of dermal-epidermal adhesion secondary to autoantibodies binding are not fully understood. Herein, we review in detail the current concepts and controversies on the complex pathogenesis of BP, shedding light on the most recent theories emerging from the literature.